FORMS OF ORGANIZING AND HOLDING CLASSES - Fazilov Ilkhom; Maksudov Ravshvn Alievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The peculiarity of the sports training in this article is that the content of some training contains information on the tools of some section of general physical training.